Analysis of the Influence of Digital Marketing and Service Quality on Organizational Culture at St. Catholic Hospital Vincentius a Paulo Surabaya City - Priyo Utomo (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Health is a right of every citizen, so the hospital's strategy for improving services should see opportunities from various aspects, especially in today's digital era. The purpose of this study is to ascertain how digital advertising and quality of service affect consumer choice to choose health services through organizational culture at St. Vincentius A Paulo City of Surabaya. Design/methodology/approach: This study's methodology brings together a descriptive technique with a quantitative approach. Customers who submitted their information into the database compose the population in the present research. The sample in this research is 200 respondents. Data collection techniques used questionnaires distributed to consumers who served as participants in tests. Analyzing data technique with path analysis method. Findings: The findings revealed that the quality of service (X2) and digital advertising (X1) had a favorable and considerable impact on organizational culture (Y) at St. Vincentius A Paulo / RKZ Surabaya City where X1 = 0.000 and X2 = 0.000 is less than 0.05. Practical implications, as input to the hospital for material evaluation of organizational culture development policies in the St. Vincentius A Paulo City of Surabaya. Theoretical repercussions, serving as a resource for future research on fundamental research of institutional cultures as input to the hospital for material evaluation of organizational culture development policies in the St. Vincentius A Paulo City of Surabaya. Theoretical repercussions, serving as a resource for future research on fundamental research of institutional cultures as input to the hospital for material evaluation of organizational culture development policies in the St. Vincentius A Paulo City of Surabaya. Theoretical repercussions, serving as a resource for future research on fundamental research of institutional cultures. Paper type: Research Paper